2022
DOI: 10.31557/apjcp.2022.23.11.3771
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Micro-RNA-423 Gene Variation on Risk and Characteristics of Breast Cancer

Abstract: Background: Micro-RNAs (miRNAs) are post-transcriptional regulators of gene expression that are abundantly expressed in a variety of cancers, including breast cancer. The mechanism of miRNAs in breast cancer oncogenesis is poorly understood. The goal of this study was to determine if there was a link between the miR-423 rs6505162 gene variation and breast cancer susceptibility among Egyptian patients. Methods: This was a case control study that included 120 female patients with pathologically confirmed breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In breast cancer, studies reporting the association between rs6505162 and cancer risk have come to contradictory conclusions. Smith et al showed that the CC genotype was linked to a reduced risk of breast cancer in Caucasian women (odds ratio, OR = 0.50; p = 0.03) [42], and the A allele was reported as a risk factor in the pathogenesis of breast cancer among the Egyptian population (OR = 3.28, p = 0.002; OR = 2.11, p = 0.011; for AA and CA against CC patients, respectively) [43]. In contrast, the CC genotype of rs6506162 was reported to be associated with an increased risk of breast cancer in Iranian women (OR = 2.37; p = 0.0023) [44].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, studies reporting the association between rs6505162 and cancer risk have come to contradictory conclusions. Smith et al showed that the CC genotype was linked to a reduced risk of breast cancer in Caucasian women (odds ratio, OR = 0.50; p = 0.03) [42], and the A allele was reported as a risk factor in the pathogenesis of breast cancer among the Egyptian population (OR = 3.28, p = 0.002; OR = 2.11, p = 0.011; for AA and CA against CC patients, respectively) [43]. In contrast, the CC genotype of rs6506162 was reported to be associated with an increased risk of breast cancer in Iranian women (OR = 2.37; p = 0.0023) [44].…”
Section: Discussionmentioning
confidence: 99%